Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1440-1754.1998.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term neurological outcomes following neonatal chest physiotherapy

Abstract: We could find no evidence that chest physiotherapy, as given in our unit, was associated with abnormal neurological outcomes in extremely preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
3
14
1
8
Order By: Relevance
“…Besides the scarce benefits, some authors have suggested that ARP might entail the risk of a neurologic damage, especially in neonates whose weight is <1500 grams, a risk which other studies did not confirm [4,8,13-18]. …”
Section: Discussionmentioning
confidence: 99%
“…Besides the scarce benefits, some authors have suggested that ARP might entail the risk of a neurologic damage, especially in neonates whose weight is <1500 grams, a risk which other studies did not confirm [4,8,13-18]. …”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] No wonder that conventional CPT gives poor results and is poorly tolerated, with side effects such as esophageal reflux, tachypnea, tachycardia, hypoxemia, rib fracture, and severe central nervous system complications, especially in newborns. [30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended. [35][36][37] In France, increased-exhalation technique has been widely used in various ways since the 1970s.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…Since this publication, several authors have disputed the association between ECPE and CPT. Beeby [9] found no evidence that chest physiotherapy was associated with abnormal neurological outcomes in extremely preterm infants. The recent article by Harding and associate [10] also found similar results as Beeby.…”
Section: Discussionmentioning
confidence: 98%